Community, family and leisure immersion. Issue 1 (2nd January 2016) - Harmon, Justin; Kyle, Gerard T.
ABSTRACT: This study explores the ambiguous term 'community' and how close groups of people come to form one. By extracting two core elements, often attributed to designations of community, mutual affection and shared appreciation, this study elucidates how fans of the rock band Jerry Joseph & the Jackmormons established close bonds referred to as family through their lengthy and passionate involvement in the leisure outlet of a music scene. Due to extensive personal involvements in various music scenes, fans ultimately came to find the music and coterie of Jerry Joseph & the Jackmormons as a place where they could address their individual needs in the comfort of like-minded others who, over time, came to define the closeness of their relationships as family through shared love of music, interaction and care for each other's well-being.